Machining error decomposition and compensation of complicated surfaces by EMD method. (February 2018) - Chen, Yueping; Tang, Hui; Tang, Qingchun; Zhang, Anshe; Chen, Dawei; Li, Kehui
Highlights: The compensation for systematic errors is the key to compensate machining errors. Machining errors are decomposed into systematic and random errors by EMD method. Systematic errors. are extracted by using autocorrelation and spectral analyses. EMD machining error compensation method improved machining accuracy significantly. Abstract: Complex surface parts are widely used in aerospace, automotive, and precision molds. Modern manufacturing aims to improve the machining accuracy and efficiency of these parts. The machining accuracy of surface parts can be significantly improved using a series of error compensation technologies to compensate for machining errors. Based on the analysis of the measurement data of the parts, empirical mode decomposition (EMD) method is used to decompose the machining errors into systematic and random errors, which are used to modify the numerical control (NC) codes to compensate for the systematic errors of the surface parts. An example of a complicated surface part proves that the method proposed in the current study can effectively improve the machining accuracy of surface parts.